Mathematical simulation for squeezing blood-based hybrid nanofluid between two permeable surfaces with the influence of MHD and viscous dissipation - Rehman, Ali; Aziz Saad, Abdullah; İnç, Mustafa; Sudarmozhi, K. (Taylor & Francis Ltd, 2025)
This research study aims to present an inclusive mathematical simulation of the squeezing flow behaviour of a blood-based hybrid nanofluid (HNF) confined in a channel. Considering a magnetic field (MF) and viscous dissipation. Blood is used as a base fluid, enhanced with two distinct nanoparticles $ A{l_2}{O_2}\,and\,Mo{S_2} $ Al2O2andMoS2 to capture advanced thermal and flow characteristics relevant to biomedical and engineering applications. For the first time this model is treated semi numerically with non-Newtonian hybrid nanofluid and viscous dissipation. For validation, the present results are compared to the already published work. The governing nonlinear PDEs are summary to nonlinear ODEs via similarity alterations, which are then solved by HAM, guaranteeing high accuracy and convergence. The impact of key parameters, MF strength, permeability, nanoparticle volume fraction, energy generation, and Eckert number on velocity and energy profiles is thoroughly analyzed. Results demonstrate that the nanoparticles' volume friction and viscous dissipation significantly enhance thermal conductivity while reducing flow velocity. Moreover, hybrid nanoparticles improve heat transfer efficiency compared to mono-nanoparticle formulations. One of the most important needs in industrial technology is ultrahigh-performance cooling. In order to improve the fluid's thermal conductivity, a new heat transfer fluid called hybrid nanofluid is created and examined using a number of physical characteristics. Furthermore, the current research work contributes to the optimization of microfluidic biomedical devices and targeted drug delivery systems by elucidating the complex interplay of MHD, thermal, and porous medium effects in HNF dynamics.
Keywords: Squeezing flow; homotopy analysis method; MHD